Foot‐and‐mouth disease viruses of the O/ME‐SA/Ind‐2001e sublineage in Pakistan. Issue 6 (22nd May 2021) - Jamal, Syed M.; Khan, Salman; Knowles, Nick J.; Wadsworth, Jemma; Hicks, Hayley M.; Mioulet, Valérie; Bin‐Tarif, Abdelghani; Ludi, Anna B.; Shah, Syed Asad Ali; Abubakar, Muhammad; Manzoor, Shumaila; Afzal, Muhammad; et al.
Abstract: The presence of foot‐and‐mouth disease virus (FMDV) of the O/ME‐SA/Ind‐2001e sublineage within Pakistan was initially detected in two samples collected during 2019. Analysis of further serotype O FMDVs responsible for disease outbreaks in 2019–2020 in the country has now identified the spread of this sublineage to 10 districts within two separate provinces in North‐Eastern and North‐Western Pakistan. Phylogenetic analysis indicates that these viruses are closely related to those circulating in Bhutan, Nepal and India. The VP1 coding sequences of these viruses from Pakistan belong to three distinct clusters, which may indicate multiple introductions of this virus sublineage, although the routes of introduction are unknown. Vaccine matching studies against O1 Manisa, O 3039 and O TUR/5/2009 support the suitability of existing vaccine strains to control current field outbreaks, but further studies are warranted to monitor the spread and evolution of the O/ME‐SA/Ind‐2001e sublineage in the region. (145 words).